Species-Associated Differences in the Inhibition of Propofol Glucuronidation by Magnolol - Yang, Lu (American Association for Laboratory Animal Science, 2014)
Magnolol, a major active constituent in herbal medicine, potently inhibits propofol glucuronidation in human liver microsomes, with inhibition constants in the nanomolar range. This study was conducted to investigate magnolol-induced inhibition of propofol glucuronidation in liver microsomes from Swiss–Hauschka mice, Sprague–Dawley rats, Chinese Bama pigs, and cynomolgus macaques. Results indicated that magnolol (10 μM) inhibited propofol glucuronidation in liver microsomes from Bama pigs and cynomolgus macaques but not in those from mice or rats. Data from liver microsomes from Bama pigs indicated a competitive inhibition mechanism, with a K(i) of 1.7 μM. In contrast to that of pig liver microsomes, the inhibition of microsomes from cynomolgus macaques followed a noncompetitive mechanism, with a K(i) of 3.4 μM. In summary, this study indicates that magnolol-induced inhibition of propofol glucuronidation varies substantially among species, and the K(i) values determined by using liver microsomes from various experimental animal species far exceed that for human liver microsomes. The inhibition of propofol glucuronidation by magnolol in liver microsomes from all animal species tested was significantly lower than the inhibition previously demonstrated in human liver microsomes. Hepatic microsomes from Swiss–Hauschka mice, Sprague–Dawley rats, Chinese Bama pigs, and cynomolgus macaques are not effective models of the inhibition of glucuronidation induced by magnolol in humans.